2013
DOI: 10.1186/1471-2318-13-36
|View full text |Cite
|
Sign up to set email alerts
|

The association between serious upper gastrointestinal bleeding and incident bisphosphonate use: a population-based nested cohort study

Abstract: BackgroundOral bisphosphonates are commonly used to prevent / treat osteoporosis. However, bisphosphonate treatment is not without risk and serious adverse effects, including upper gastrointestinal bleeding (UGIB) have been described. We sought to determine if new users of bisphosphonate drugs were more likely to suffer a serious UGIB within 120 days of drug initiation.MethodsThis was a population-based nested cohort study utilizing administrative healthcare data in British Columbia, Canada. Community based in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 52 publications
2
29
0
2
Order By: Relevance
“…Oral bisphosphonates can cause gastroesophageal side effects in patients. 377 Oral agents should not be used in patients with Barrett esophagitis, as these patients are at increased risk of esophageal cancer and any additional esophageal irritation should be avoided. Intravenous bisphosphonates are generally used when patients experience GI intolerance to oral agents or when patients have difficulty maintaining compliance with medication regimens (dementia and polypharmacy) and a notation of these reasons may be needed when applying for insurance approval.…”
Section: Treatment Of Osteoporosismentioning
confidence: 99%
“…Oral bisphosphonates can cause gastroesophageal side effects in patients. 377 Oral agents should not be used in patients with Barrett esophagitis, as these patients are at increased risk of esophageal cancer and any additional esophageal irritation should be avoided. Intravenous bisphosphonates are generally used when patients experience GI intolerance to oral agents or when patients have difficulty maintaining compliance with medication regimens (dementia and polypharmacy) and a notation of these reasons may be needed when applying for insurance approval.…”
Section: Treatment Of Osteoporosismentioning
confidence: 99%
“…When OVX rats were injected weekly with alendronate, gastric injury has become evident, while antioxidant GSH levels were depleted. Despite the well-established side effects of the oral form on the upper gastrointestinal tract, 4 the injurious effect of parenteral alendronate was not documented before. Our findings also demonstrated that melatonin reduced gastric inflammation by depressing neutrophil infiltration and lipid peroxidation, and these receptor-independent effects of melatonin possibly depend on its radical scavenging actions.…”
Section: Figurementioning
confidence: 99%
“…1 Primary target in the treatment of osteoporosis is to reduce pain, to reduce the risk of fracture, and to improve impaired functions. 2 Since the anticatabolic bisphosphonate alendronate maintains bone mass via the inhibition of osteoclastic activity, it is the first-line medical treatment in post-menopausal osteoporosis 3,4 , during which disrupted bone remodelling with an accelerated bone resorption occurs due to the absence of oestrogen. 5 Despite its considerably safe and tolerable use, some side effects associated with its long-term or parenteral use, including gastrointestinal adverse events, [6][7][8] acute phase reaction, hypocalcaemia, osteonecrosis, and atypical fractures of jaw 9,10 were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies reported that patients taking oral bisphosphonates develop upper gastrointestinal symptoms, [14][15][16] recent studies have failed to find a relationship between the use of oral bisphosphonates and upper gastrointestinal symptoms. [17][18][19][20] Conversely, upper gastrointestinal symptoms were not associated with the administration of oral bisphosphonates.…”
Section: Introductionmentioning
confidence: 96%